Pengaruh kecerdasan emosional dan kepribadian terhadap tingkat pemahaman akuntansi (studi empiris pada mahasiswa akuntansi fakultas ekonomi universitas riau) - Febri Yulisa; Kamaliah '; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine how the effect of the variable component ofemotional intelligence is self awareness, self regulation, motivation, empathy, social skills and personality to the level understanding of accountancy.Measuring instrument to measure storey level understanding of accountancy is average point of accountancy that is PA1, PA2, AK1, AK2, AKL1, AKL2, AU1, AU2, and TA. As for the population in this study was a class of 2010 student of Accounting Department of Economics, University of Riau, amounting to 316 students, and in this study as the samples totaling 76 students using Slovin formula. Analysis of the data used is descriptive analysis, as it also uses the quantitative analysis using multiple linear regression with the help of SPSS program version 20.00.From the test results have shown that the introduction of the variable selfawareness has no effect on the level understanding of accounting, whereas for the variable self regulation, motivation, empathy and social skills as well as personality influence on level of understanding accounting.Many other factors which influence storey level understanding of accountancy factors like mental stress, and etc. Result of this research can give contribution to university in order to compiling curriculum and can give input to the student in order to developing emotional intelligence.Keywords: self awareness, self regulation, motivation, empathy, social skills, personality, level understanding of accountancy.